The Long or the Post of It? Temporality, Suffering, and Uncertainty in Narratives Following COVID-19 - Cheston Katharine; Cenedese Marta-Laura; Woods Angela (Springer, 2025)
Long COVID affects millions of individuals worldwide but remains poorly understood and contested. This article turns to accounts of patients’ experiences to ask: What might narrative be doing both to long COVID and for those who live with the condition? What particular narrative strategies were present in 2020, as millions of people became ill, en masse, with a novel virus, which have prevailed three years after the first lockdowns? And what can this tell us about illness and narrative and about the importance of literary critical approaches to the topic in a digital, post-pandemic age? Through a close reading of journalist Lucy Adams’s autobiographical accounts of long COVID, this article explores the interplay between individual illness narratives and the collective narrativizing (or making) of an illness. Our focus on temporality and suffering knits together the phenomenological and the social with the aim of opening up Adams’s narrative and ascertaining a deeper understanding of what it means to live with the condition. Finally, we look to the stories currently circulating around long COVID and consider how illness narratives—and open, curious, patient-centered approaches to them—might shape medicine, patient involvement, and critical medical humanities research.